National Dialogue: Bahrain Case - E. I. Vulakh (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The all-inclusive interparty negotiations on a national basis aimed at ending an internal conflict, overcoming its consequences and securing conditions for a peaceful development of the society are not by themselves a new phenomenon. At the same time this format, generally referred to as a ‘national dialogue’, has recently gained a new impetus, particularly in the Asian and African countries, affected by the Arab Awakening. Despite this fact the very definition of a ‘national dialogue’ remains vague, both scholars and policy practitioners still lack an adequate and precise understanding of its aims, mechanisms and implications. In order to provide a better understanding of the concept of a ‘national dialogue’, the author summarizes the most widely accepted definitions and considers them by reference to a concrete country case. As such, the author examines the national dialogue initiated by Bahrain’s authorities in the face of the Arab Awakening. The author concludes that in its most general sense the national dialogue implies an attempt to unify the efforts of all conflicting parties and actors (both state and non-state) to promote a national consensus on the key issues of reconciliation. In that context both the key task of and the major challenge to the national dialogue is to ensure maximal inclusiveness. In order to do so a few methodological, as well as purely practical questions need to be addressed: interests of what political forces (groups) must be considered, who is to elaborate the criteria and methods of selecting actual participants of the negotiations, how to assess their real representativeness and legitimacy and so on. It is from this perspective that the paper assesses Bahrain’s experience in organizing the national dialogue. The paper describes in detail a preparatory process for negotiations, their key participants, and their progress. The author concludes that though experts traditionally refer to Bahrain’s national dialogue as, at best, unsuccessful, its more detailed examination allows to reevaluate some of its aspects. The modest success of negotiations is explained by both subjective (the position of the ruling elites and their political opponents) and objective factors (a highly polarized and conflictual nature of the society). Nevertheless, the dialogue managed to reduce the level of political tension in the country and this experience could prove very useful.